(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Pavements experience numerous distresses including rutting, fatigue cracking, ravelling, etc. as a result of rising axle loads, rising traffic volumes, and poor maintenance. These annoyances lengthen travel times and raise maintenance costs for automobiles while lowering the pavement’s riding quality. By incorporating various additives like polymers, nanomaterials, and other compounds into bitumen, one can improve the desirable qualities of the bitumen binder and so lessen the likelihood of these distresses occurring. Although they have demonstrated beneficial benefits on bitumen, polymer additives including polyethylene, ethylene-butyl acrylate (EBA), and styrene-butadiene-styrene (SBS) have certain downsides, such as low storage stability[2]. More study is currently being done to determine how utilising nanoparticles can improve the performance of pavements. Nanomaterials are advantageous because they have a lot of surface area and good dispersion.